(untitled) (KONFERENSIYA, 2026)
In the context of the current reforms in the education system, the formation of ecological culture in students’ psychology has become an urgent requirement of the time. Human development is closely interconnected with the natural, social, and cultural environment, and this process begins from the earliest stages under the influence of family, education, and society. Historical sources, including the works of Abu Rayhan Beruni, emphasize the decisive role of geographical and natural conditions in shaping both the physical and psychological characteristics of individuals. In the modern era, global ecological challenges-such as atmospheric stagnation, ozone layer depletion, freshwater scarcity, deforestation, and waste pollution-further necessitate the cultivation of ecological education and culture.